Analisis Pemahaman Awal Guru Fisika SMA se-Kabupaten Padang Pariaman Terhadap Konsep Bahan Ajar Scientific - Fanny Rahmatina Rahim (Pelita Eksakta, 2019)
The teacher faces many problems in implementing the latest curriculum in Indonesia. The main problem is the provision of teaching materials based on scientific approaches. Teaching materials that are well designed according to the characteristics and objectives of learning. The aim is to develop students' thinking skills. For this reason, it is necessary to compile Scientific Model teaching materials that can increase HOTS students. A more appropriate action was to provide technical guidance in making Scientific Model teaching materials to Physics teachers through the Physics teacher working group. The partners in this activity were the working group of Physics Teachers in Padang Pariaman Regency. Based on the results of data analysis, there were many teachers who have not fully understood about making scientific material.